2019
DOI: 10.48550/arxiv.1912.04683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A variance for $k$-free numbers in arithmetic progressions of given modulus

Abstract: LetS = {n ∈ N| there is no prime p with p k |n}, the set of k-free numbers. For some suitable main term η(q, a) to be defined soon enough we will study in this paper the object q a=1

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…Once extended to composite q our Theorem 2 improves on results by Warlimont [War80] and Vaughan [Vau05] who obtain an asymptotic formula with an additional averaging over q ≤ Q in the range x 2/3 ≤ Q = o(x). Moreover Theorem 2 improves on a succession of results by Blomer [Blo08], Nunes [Nun15] (see also [Par19]) and Le Boudec [LB18] who considered individual averages over (a, q) = 1 as we do in Theorem 2. In particular Nunes showed that (7) holds in the range x 31/41+ε ≤ q = o(x) and Le Boudec showed that the left-hand side of ( 7) is O ε ((x/q) 1/2+ε ) for all ε > 0 in the range x 1/2 ≤ q ≤ x.…”
supporting
confidence: 68%
“…Once extended to composite q our Theorem 2 improves on results by Warlimont [War80] and Vaughan [Vau05] who obtain an asymptotic formula with an additional averaging over q ≤ Q in the range x 2/3 ≤ Q = o(x). Moreover Theorem 2 improves on a succession of results by Blomer [Blo08], Nunes [Nun15] (see also [Par19]) and Le Boudec [LB18] who considered individual averages over (a, q) = 1 as we do in Theorem 2. In particular Nunes showed that (7) holds in the range x 31/41+ε ≤ q = o(x) and Le Boudec showed that the left-hand side of ( 7) is O ε ((x/q) 1/2+ε ) for all ε > 0 in the range x 1/2 ≤ q ≤ x.…”
supporting
confidence: 68%